Challenges in sustaining old shophouse in Kuala Lumpur / Nur Salfarina Fauzi - Fauzi, Nur Salfarina (Faculty of Architecture, Planning and Surveying, 2015)
This research paper is about a study on the challenges in sustaining the old shophouses in Kuala Lumpur. Kuala Lumpur was chosen because it is where the modernisation and new development rapidly take place. This can be seen as a threat to the heritage buildings especially old shophouses in Malaysia. Old shophouse is a part of heritage buildings that represents culture, economic activites and story of the cities. A shop in South East Asia is defined as a building with an opening onto the pavement and the proprietor occupies the building. The significance of the old shophouses can be considered as a type of heritage to urban form and townscape of a place and has a unique architecture that represents the aesthetic of a culture. The main objective of this study is to investigate the challenges in sustaining old shophouses located in a city where modernisation takes place. The outcome of the study is hoped to help overcome any challenges in maintaining and conserving the unique architecture. The methods used in this research are open interview involving the local citizen and questionairre survey for the tenants or owner of the old shophouses.